The future of the Korean peninsula : Korea 2032 and beyond - Richey, Mason; Panda, Jagannath P.; Tizzard, David A. (New York : Routledge, 2022)
"This book considers both Koreas - North Korea and South Korea - to examine possible pathways for the years leading up to 2032 and beyond, thus offering a composite picture of Korea and its strategic relevance in Asia and the world at large. With the announcement of the two Koreas seeking a joint Olympic bid for 2032, this book takes the opportunity to revisit the history of the Koreas in a comparative contemporary context. This book does so by treating both Koreas as closely connected-rather than divided-in order to better understand and forecast their relevance and rise in both an Asian and global context. Chapters begin with a brief historical review and analysis of the present, before moving to consider how these will shape the next decade, drawing comparative and complementary analyses. No matter how contrasting the contemporary trajectories of both North and South Korea might appear, 'Korea' as a singular entity is an old concept still containing great possibilities. As the ongoing inter-Korean reconciliation process underscores, the futures of North and South Korea can be found in a complementary singular Korea, which would again represent an important political, strategic, cultural, and social space in Asia. An evaluation of the future trajectory, social awareness and perception of the Koreas, this book offers a valuable contribution to the study of North and South Korea and Asian Politics"--
Includes bibliographical references and index.
Keywords: Ethnology -- Korea; Korea (South) -- Foreign relations; Korea -- Economic policy